Éditorial: Le média, le massage et le marché - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
NTIC ont ouvert la voi à une nouvelle génération de services d´information ? multi-modales ?.